(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that social networks are an external (technological, digital) expression of deep transformational processes at the level of consciousness of both an individual and collective consciousness, changing not only the technical processes of information transmission, their speed, convenience and accessibility, but also more deep, multifaceted thinking processes of people, awareness of one’s own identity in a multipolar world of multiple truths, where manifestations of criminality are so easily interwoven into worldview voids. It is noted that social networks in their modern understanding are increasingly losing their communicative significance, acting more as a means of organizing leisure time, instant receipt of unstructured information adapted to the needs and interests of an individual person. To a large extent, this is related to the rethinking of communication itself, which is increasingly becoming visual in nature. It is argued that due to accessibility, openness to any content, age and social groups, social networks become a platform for manifestations of crime. Within social networks, communities of deviant behavior can also form, which unite people around certain deviant behaviors, behaviors that are generally considered inappropriate in terms of societal norms or moral standards. Deviant social networks are particularly dangerous among children and adolescents. Attention is focused on the fact that social networks can also be used in the course of information and psychological operations aimed at manipulating mass consciousness. Deepfake techniques are actively used by the aggressor state to create videos and images on social networks that somehow discredit the Ukrainian government, as well as the security and defense forces. Similar technologies are also used to justify the commission of war crimes on the territory of Ukraine.